You are on page 1of 7

2

2.1 (. 10)
1.

f ( x ) = 5x4

2.

f (x) =

3.

f (x) =

4.

f ( x ) = ex +

5.

f (x) =

6.

f ( t ) = 3t2 + 6t - 1, f ( t ) = 6t + 6

7.

f ( t ) = t3 e t , f ( t ) = 3t2 e t + t3 e t = e t ( 3t2 + t3 )

8.

f ( x ) = ( 2e x - 3 ) x2 , f ( x ) = 2e x x2 + ( 2e x - 3 ) 2x = 2e x x2 + 4e x x - 6x

1
4
= x-4 , f ( x ) = -4x-5 = - 5
4
x
x
3

x3 = x 2 , f ( x ) =

3 21
3
x =
x
2
2

1
2
= e x + x-2 , f ( x ) = e x - 2x-3 = e x - 3
2
x
x
12x2 - 10x
2 4 x 3 - 5x2

6x 2 - 5x
4 x 3 - 5x 2

itu

= 2x ( xe x + 2e x - 3 )

inD

2 4 x 3 - 5x 2

-2 ( x2 + 1 ) - ( 1 - 2x ) 2x
1 - 2x
2x2 - 2x - 2

,
f
x
=
=
(
)
2
2
x2 + 1
( x2 + 1 )
( x2 + 1 )

10.

f ( t ) = t t, f ( t ) = 1 t + t 2t = t + t 2t

11.

f ( x ) = e x x, f ( x ) = e x x + e x x = e x ( x + x )

12.

f ( x ) = x2 x, f ( x ) = 2xx + x2xx = xx ( 2 + xx )

13.

-xx ( 1 + x ) - x ( -2x )
x
f (x) =
, f ( x ) =
1 + x
( 1 + x )2

f ( ) =

In

x ( 1 - x )
( 1 + x )2

( 1 + ) - ( 1 - )
2 + 2 + -
1 -
=
, f ( ) =
1 +
( 1 + )2
( 1 + )2

1 + -
( 1 + )2

Pr

at

( 1 + x )

Cl
2

iv

14.

x ( -x - 2x + 2x )

st

f (x) =

ev

9.

te

( 4x3 - 5x2 )

er
M

4x 3 - 5x2 , f ( x ) =

15. y = ( 3x ) ,

dy
= ( 3x ) ( 3x ) = 3 ( 3x )
dx

16. y = ( 2x ) ,

dy
= - ( 2x ) ( 2x ) = - 21 ( 2x )
dx

( x2 + 5 )

17.

f ( x ) = ( x2 + 5 ) , f ( x ) = 5 ( x2 + 5 )

18.

f ( ) = 2 , f ( ) = 2 ( ) = 2

19. y = x3 x,

= 10 x ( x2 + 5 )

dy
= 1 3 x + x 32x ( x ) = 3 x + 3x2x2x = 2x ( x + 3x2x )
dx

20. y = e x 2x,
21.

dy
= e x 2x + e x 2x ( x ) = e x x ( x + 2x )
dx

f ( t ) = t22t, f ( t ) = 2t ( 2t ) + t2 ( 2t )( 2t ) = 2t ( ( 2t ) + t ( 2t ) )

22. y =

( 2x + x ) 2xx - x x ( 2x - 1 )
dy
=
=
=
x + x ,
dx
2 2x + x
2 2 x + x
2 2x + x

23. y =

1 + 2 ( 3x ),

dy
( 1 + 2 ( 3x ) )
-2 ( 3x ) ( 3x )
=
=
=
dx
2 1 + 2 ( 3x )
2 1 + 2 ( 3x )

-3 ( 3x )
1 + 2 ( 3x )

dy
= ( ( 2x ) ) ( ( 2x ) ) = ( ( 2x ) ) ( -2 ( 2x ) )
dx

24. y = ( ( 2x ) ) ,

= -2 ( 2x ) ( ( 2x ) )

= 4 ( xx )3 ( x - x2x )

( ex
3

+e

-x 2

1 + x 3 = ( 1 + x 3 )3 ,

2e x 2e-x

( ex

+e

28. x2 + y2 = 1, 2x + 2y

( ex

+ e -x )

-2
2
dy
1
= ( 1 + x 3 ) 3 ( 1 + x 3 ) = x2 ( 1 + x 3 ) 3
dx
3

dy
dy
x
=0
=dx
dx
y

dy
dy
2
=4
=
dx
dx
y

Cl

29. y2 = 4x, 2y

-x 2

ev

27. y =

itu

st

+ e -x ) - ( e x - e -x )

In

( ex

er
M

( e x - e-x ) ( e x + e-x ) - ( e x - e-x )( e x + e-x )

dy
e x - e -x
26. y = x
=
,
2
dx
e + e -x
( e x + e -x )

te

dy
= 4 ( xx )3 ( xx ) = 4 ( xx )3 ( x + x ( -2x ) )
dx

inD

25. y = ( x x )4 ,

at

dy
-( x + y )
=
dx
x-y

iv

dy
dy
dy

30. x2 + 2xy - y2 = 8, 2x + 2 1 y + x - 2y
= 0 ( 2x - 2y )
= -2x - 2y

dx
dx
dx

dy
( 3x + 4 )
3
=
=
dx
3x + 4
3x + 4

Pr

31. y = ln ( 3x + 4 ) ,
32. y = ln ( x ) ,

33. y = ln ( e + e
x

-x

dy
( x )
x
=
=
= x
dx
x
x

( e x + e-x ) e x - e-x
dy
) , dx = x -x = x -x
e +e
e +e

34. y = ln ( x3x ) ,

( x3x ) 3x2x + x3 ( -x ) 3x - xx
dy
=
=
=
dx
xx
x 3x
x 3x

35. y = log 3x2 - 5 =

=

3x
( 3x - 5 ) ln 10
2

36. y = 2x ,
37.

dy
1 ( 3x - 5 )
1
6x
1
log ( 3x2 - 5 ) ,
=
=
2 ( 3x2 - 5 ) ln 10
2 ( 3x2 - 5 ) ln 10
2
dx

dy
= 2x ln 2
dx

f ( ) = a , f ( ) = a ln a ( ) = - a ln a

38. y = 2x

+1

2
2
dy
= 2x +1 ln 2 ( x2 + 1 ) = 2x 2x +1 ln 2
dx

39. y = x x ln y = x ln x,

y
1
= 1 lnx+ x y = y ( ln x + 1 ) = x x ( ln x + 1 )
y
x

1
= x- , f ( x ) = -x--1 , f ( x ) = ( + 1 ) x--2 , f ( x ) = - ( + 1 )( + 2 ) x--3
x

( + 1 )( + 2 )
x + 3

ev

=-

43. y2 - 2xy = 2, 2y
dy
y
dx (

- x) - y

dy
dy
dy
dy
y

- 2 y + x = 0 ( 2y - 2x )
= 2y
=

dx
dx
dx
dx
y-x

( dydx - 1 ) =

y
y-x

Cl

d2 y
=
dx2

d
dt

d2 y
=
dx2

at

3t2

d
d

- ( 6t + 10 )
18t2 - 36t2 - 30t
-18t2 - 30t
=
=
6
6
27t
27t
9t5

dy
dx
= -2. y = 2,
= 2.
d
d

2
= -
-2

( dydx ) = 2 = dx
d

-2

1
23

yx
y-x
2

(y - x)

( y - x )2

y-

dy
dx
= 3t2 . y = 3t2 + 5t + 1,
= 6t + 5.
dt
dt

( dxdy ) = 63t -(96t t +5 )6t

dx
dy

dy
d
dx
d

( y-y-y +x x ) =

6t + 5
3t2

() x = 2 ,
dy
=
dx

( y - x )2

y-y

Pr

d2 y
=
dx2

dy
dt
dx
dt

( y-y x - 1 ) =

iv

() x = t3 + 2,
dy
=
dx

(y - x) - y

( y - x )2

2.2 (. 13)
1.

d3 y
= -6 ( 1 + x )-4 ,
dx 3

st

42. f ( x ) =

er
M

d4 y
24
= 24 ( 1 + x )-5 =
4
dx
( 1 + x )5

d2 y
= 2 ( 1 + x )-3 ,
dx2

te

dy
= -1 ( 1 + x )-2 ,
dx

itu

1
= ( 1 + x )-1 ,
1+x

In

41. y =

inD

40. y = 2x6 , y = 12x5 , y = 60x4 , y = 240x 3 , y( 4 ) = 720x2 , y( 5 ) = 1440x, y( 6 ) = 1440

y2 - 2xy

( y - x )3

() x = 3t,

( dxdy ) = - 23 ( -3t-4 ) =
dx
dt

d2 y
=
dx2

dy
dt
dx
dt

d
dt

dy
dx
= t. y = ( 2t ) ,
= - ( 2t ) ( 2t ) = -2 ( 2t ) .
dt
dt

-2 ( 2t )
-2t t
=
= -2t
t
t

( dxdy ) = -2t = -2 d2 y + 2 = 0.
dx
dt

dx2

dx
1 ( 1 + 2t ) - ( 2 + t ) 2
-3
2+t
=
=
,
2
1 + 2t
dt
( 1 + 2t )2
( 1 + 2t )

y=

dy
3 + 2t
3
-3
= + 2,
= 2
t
t
dt
t

-3
( 1+2t )2

2 ( 1 + 2t )4
3t3

x =0

d2 y
dx2

x = e t ,

x2

3 ( -2 )

dy
= t
dt

=-

d
dt

( dxdy ) = e-t ( -t ) t + e-t ( -t ) = -t - t

dx
dt

et

e 2t

d2 y
dy
-t - t
t
+x
+ y = e 2t
+ e t t + t = -t - t + t + t = 0
2
2
t
dx
dx
e
e

2.3 (. 15)
1.

27
4

2t ( 1 + 2t )( 2t - 1 - 2t )( 1 + 2t )3
3t4

t
= e-t t
et

Pr

d2 y
=
dx2

dy
dt
dx
dt

t =-2

2 ( -3 )4

dx
= et
dt

y = t,
dy
=
dx

at

t4
3
( 1+2t )2

iv

d2 y
dx2

st

( dxdy ) = 2(1+2t )( 2t )tt -(1+2t ) 2t

dx
dt

itu

( 1 + 2t )2
t2

In

d
dt

Cl

-3
t2
-3
( 1+ 2t )2

d2 y
=
dx2

dy
dt
dx
dt

er
M

x=

dy
=
dx

4.

2
3t4

x = t,

dy
=
dx

3.

d
dt

-2t-3
2
=- 3
3
3t

ev

2.

te

d2 y
=
dx2

dy
dt
dx
dt

inD

dy
=
dx

dy
dx
1
= 3. y = 2 = t-2 ,
= -2t-3
dt
dt
t

y = x2 + 3x, dy = ( 2x + 3 ) dx

2.

x = , dx = d

3.

u=

4.

u = 2, du = 2 ( ) d = 2 ( - ) d = -2d

5.

y = ( 7 - 2x3 ) , dy = 4 ( 7 - 2x 3 )

( x2 + 1 )
2 x +1
2

y =

( 11-+xx )
1-x
dy
dx =
=
,
x
1+x
2 11+x

x +1
2

( 7 - 2x3 ) dx

( 1+ x )2
1- x
1+ x

dx =

-2 1 + x
2

2(1 + x )

1-x

dx =

-1
3

( 1 + x )2 1 - x

dx

-dx

x =-2

() y = ( 2x ) ,

1
4

= -4 =

1
4

er
M

dy
dy
1
1
,
= - 2 . =
dx
x
dx
x

= -4 =

x = 21

dy
dy
= ( 2x ) ( 2x ) = 2 ( 2x ) . =
dx
dx

ev

:
2x + 2y

itu

dy
dy
= 2x. =
dx
dx

dy
dy
dy
x
=0
= - . =
dx
dx
dx
y

( x , y )=( 1,4 )

Cl

x = 2

= -2 =

1
2

st

() y = x2 ,

te

( 1 + x ) 1 - x2

() y =

2.

= -24x2 ( 7 - 2x 3 ) dx

-1( 1+ x )-( 1- x )1

2.4 (. 20)
1.

dx

inD

dx =

1
=- .
4

In

6.

x + 1, du =
2

1
y - y1 = ( x - x1 ) y - 4 = - ( x - 1 ) 4 y - 16 = -x + 1 x + 4 y = 17
4
:

2y dy
y2
dy
2x
2

2x
x2
1,
.
+

=
=0
.
+
=

2
2 dx
2
2
2
2
dx

iv

3.

at

= 4, y - 4 = 4 ( x - 1 ) y - 4 = 4x - 4 4x - y = 0

Pr

y - y1 = ( x - x1 ) y - = -

( x - ) y - 2 = -x + 2

x + y = ( 2 + 2 ) x + y =

4.

=1

x -1
1-1
0
()
=
=
10
x 1 x
1-1
0
-1

() lim

x -1
1
1
= lim
=
10
9
x 1 x
x 1 10 x
10
-1

, lim
3

() lim

x 4

x-34
=
x -2

4-34
0
=
()
0
4 -2

-2

1x 3
x-34
2 -1
2 -1
2 -1
2
= lim 3 1 = lim x 6 = 4 6 = 2 3 = 3
x 4 1 - 2
x 4 3
3
3
x -2
3 2
x
2

, lim

x 4

() lim

x 2

ln ( x - 1 )
ln 1
0
=
=
()
8 + 2 - 10
0
x + x - 10
3

1
ln ( x - 1 )
1
1
x -1
=
= lim
=
lim
3
2
2
x 2 x + x - 10
x 2 3x + 1
x 2 ( 3x + 1 ) ( x - 1 )
13

, lim

22
2 0
0
()
=
=
1-1
0
2 1 -

() lim

22
4 ( )
= lim
= lim ( 4 ) = 4
-
2 1 -
2
2

, lim

x0

ln x
-
=
()
ln ( x )
-

inD

() lim

er
M

e2x - 2x
1-1
0
=
=
()
x 0 e 3 x - 3x
1-1
0

() lim

itu

te

1
x
x
ln x
1
= lim x = lim
= lim

= 11 = 1
x 0 ln ( x )
x 0 ( x )
x 0 x x
x 0 x
x

, lim

e2x - 2x
2e 2x + 2 2x
21 + 2 0
2
=
lim
= lim
=
x 0 e 3 x - 3x
x 0 3e 3 x + 3 3x
x 0 3 1 + 3 0
3

, lim

ev
x

, lim xe x = lim

x - e-x

x -

-
()
+

1
1
=
=0
x
x - -e
-

Cl

lim xe x = lim
x -

In

x -

st

() lim xe x = - 0 ()

() lim x2e-x = + 0 ()

x -

x2

+
()
+

at

2
x + e x

x +

2x

lim x2e-x = lim

= lim

iv

x +

x + e x

2x

x + e x

1
=0

x0

Pr

() lim x2e x2 = 0 ( + ) ()
1

, lim x2e

1
x2

x0

= lim

e x2

x 0 12
x

+
()
+

lim x2e
x0

1
x2

= lim

x0

e x2 ( -2x-3 )
-2x-3

= lim e x2 = +
x0

() lim+ ( x ln x ) = 0 ( - ) ()
x0

, lim+ ( x ln x ) = lim+
x0

x0

ln x
-
=
()
-1
+
x

1
x

lim+ ( x ln x ) = lim+
x0

() lim

x 1

-1x-2

x0

= lim+ ( -x ) = 0
x0

ln x - x + 1
0 -1 +1
0
=
=
()
00
0
( x - 1 ) ln x
1 -1
ln x - x + 1
x
= lim
x 1 ( x - 1 ) ln x
x 1 ln x + ( x - 1 )

, lim

ln x - x + 1
-1
= lim
x 1 ( x - 1 ) ln x
x 1 ln x + x

lim

() lim+ ( x
x 0

1
x

+1

1
x

1-x
0
=
()
x 1 x ln x + x - 1
0

= lim

-1
-1
1
=
=x 1 ln x + x + 1
2
2

= lim

e ) = lim+ x e x = 0 ( + ) ()
x0

, lim+ ( x e ) = lim+
x

x0

ex

x0

1
x

+
()
+

e x ( - x12 )

x0

e ) = lim+
x0

- x12

= lim+ e x = +
x0

e x + e -x - 2
1+1-2
0
()
=
=
x 0 1 - x
1-1
0

er
M

lim

ev

In

2
1
= k 2 = 16 k = 4
2
8
k

Pr

iv

at

st

e x + e -x - 2
e x + e -x
1+1
2
= lim 2
=
= 2
2
x 0 1 - kx
x 0 k kx
k
k

, lim

itu

e x + e -x - 2
e x - e -x
1-1
0
()
= lim
=
=
x 0 1 - kx
x 0 k kx
0
0

, lim

Cl

5.

te

lim+ ( x

inD